Influence of rosuvastatin treatment on airway inflammatory markers and health related quality of life domains in asthmatic patients - CEYHAN, BERRİN; KOCAKAYA, DERYA; BALCAN, MEHMET BARAN; OLGUN YILDIZELİ, ŞEHNAZ (MARMARA UNIV, FAC MEDICINE, 2017)
Objectives: Statins are lipid lowering agents which have pleiotropic and anti-inflammatory effects. Beneficial effects of statins have been shown in many inflammatory and asthmatic diseases. However, the results are still not consistent. The aim of this study is to determine the clinical and anti-inflammatory effects of rosuvastatin in asthmatic patients. Patients and Metods: A case control study among asthmatic patients was conducted. One hundred and thirty-six participants were screened. Seventy-four patients were eligible. Fifty-one patients have completed the trial. Twenty-five patients with blood levels of low-density-lipoprotein (LDL) above 130mg/dL, were treated with rosuvastatin 40mg for 8 weeks in addition to their standard treatment for asthma; 26 asthmatic patients were followed as control group. In both groups baseline and 8th week evaluation were recorded including pulmonary function test (PFT), bronchial provocation test (PD20), induced sputum and serum inflammatory markers, asthma control test (ACT) and quality of life scores (QoL). Results: Statin group showed improvement in FEV1/FVC (pp) (85.8 +/- 11.1% vs 90.2 +/- 8.8% P<0.043), FEF 25-75 % (63.6 +/- 7.8 % vs 74.6 +/- 8.4 %, P<0.0001) and FEF25-75(L/sc) (3.51 +/- 0.4 vs 4.1 +/- 0.4 P<0.05) and no change was seen in non-statin group (P>0.05) at the end of the 8-week treatment. Treatment with rosuvastatin resulted in decreased sputum eosinophilia percentage (P<0.05); IL-6 and TNFalpha levels (P<0.05) however, bronchial challenge test, ACT and QoL domains did not change in both groups (P>0.05). Conclusion: An 8-week treatment with 40mg rosuvastatin in asthma decreased the peripheral eosinophilia, total IgE levels and inflammatory markers in the induced sputum samples. Beneficial effects in PFT have also been observed. However, ACT and QoL domains were not affected. The implication of this study is that rosuvastatin could potentially have anti-inflammatory effects on asthmatic airways. Prospective randomised trials to evalute the clinical effects of rosuvastatin are warranted.
Keywords: Asthma; Airway inflammation; Remodelling; Rosuvastatin; Statin; NECROSIS-FACTOR-ALPHA; HMG-COA REDUCTASE; ALLERGIC-ASTHMA; IN-VITRO; STATINS; ATORVASTATIN; SIMVASTATIN; INHIBITORS; SPUTUM